Metastatic Transitional Cell Carcinoma of the Bladder to the Testis: A Case Report - Gregory N. Kozak; Nicholas C. Field (Case Reports in Urology)
An 84-year-old gentleman presented with onset of gross hematuria in September 2010. Follow-up investigations revealed T1 superficially invasive, poorly differentiated, papillary urothelial carcinoma. He subsequently had GreenLight laser for BPH and bladder neck contracture on two occasions. He developed a right hydrocele 16 months after initial presentation and during his hydrocelectomy, a rock-hard right epididymis and testicle were discovered. Pathology revealed metastatic urothelial carcinoma replacing nearly the entire testis with lymphovascular invasion.